Evaluation of the Prevalence of Oral Manifestations and the Related Factors in Hemodialysis Patients at Selected Hospitals of Tehran Province in 2016 - S Alirezaei; E Razeghi; M Rezaie; N Moezi Ghadim; L Sabet Ghadam (Islamic Azad University, 2018)
Background and Aim: Halitosis, candidiasis, and metallic taste are some of the oral complications in chronic renal failure patients undergoing dialysis. The aim was to evaluate the prevalence of oral manifestations and the related factors in hemodialysis patients at selected hospitals of Tehran in 2016. Materials and Methods: This cross-sectional study was performed through observation, examination, interviewing, reviewing the medical records, and completing the information form. Oral manifestations were examined with indices of halitosis, metallic taste, and candidiasis. The presence of each indicator was considered as oral manifestations, and the measurement was standardized and performed by a student under the supervision of the respective professors. The training required for measurements was provided by the supervisor and the advisor. The reliability was measured in a seven-day pilot study. An organoleptic method was used to measure halitosis. The diagnosis of metallic taste and candidiasis was made through interviewing and observation, respectively. Results: The study was performed on 250 patients (58.8% male and 41.2% female) with the mean age of 59 years (17 to 88 years). The average duration of dialysis was 62 months. Oral manifestations were present in 91.2% of patients. The most common oral manifestation was halitosis (90%), followed by metallic taste (12%), and candidiasis (10.8%). The incidence of candidiasis was higher in older patients and denture wearers (P≥0.05). Halitosis and metallic taste did not relate to the studied factors (P≥0.2 and ≥0.9). Conclusion: The prevalence of oral manifestations in chronic kidney failure patients undergoing hemodialysis is high. Etiologic studies are recommended to understand the causes and to reduce the complications.